Austenitic stainless steel resistant to lead bismuth / supercritical carbon dioxide uniform corrosion and grain boundary oxidation and preparation method of austenitic stainless steel

By adjusting the element content and process flow in austenitic stainless steel, a new austenitic stainless steel was prepared, which solved the corrosion problems in high-temperature lead-bismuth and supercritical carbon dioxide environments, especially the grain boundary oxidation corrosion performance, achieving 650% Long-term corrosion resistance under ℃ environment.

CN119307832APending Publication Date: 2025-01-14SHANGHAI JIAOTONG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411198220.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing austenitic stainless steels have serious corrosion problems in high-temperature lead-bismuth and supercritical carbon dioxide environments, especially the phenomenon of preferential oxidation of grain boundaries leads to material failure and there are no candidate materials that are resistant to preferential intergranular oxidation corrosion.

Method used

By reasonably adjusting the content of nickel, chromium, aluminum, manganese, silicon, niobium, yttrium, carbon and other elements, a new austenitic stainless steel is prepared by vacuum induction furnace power supply and melting and forging technology, and heat treatment is carried out to improve its corrosion resistance. .

Benefits of technology

The new austenitic stainless steel exhibits good corrosion resistance in 650℃ high temperature lead-bismuth and supercritical carbon dioxide environments. The oxide film thickens small, and no obvious preferential intergranular oxidation occurs, meeting the service for up to 20-30 years. Cycle requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307832A_ABST
    Figure CN119307832A_ABST
Patent Text Reader

Abstract

The invention discloses austenitic stainless steel resistant to lead bismuth / supercritical carbon dioxide uniform corrosion and grain boundary oxidation and a preparation method of the austenitic stainless steel resistant to lead bismuth / supercritical carbon dioxide uniform corrosion and the grain boundary oxidation. The mass fraction of nickel is 12-20%, the mass fraction of chromium is 10-20%, the mass fraction of aluminum is 1.5-4.5%, the mass fraction of manganese is 1-4%, the mass fraction of silicon is 0.5-1%, the mass fraction of niobium is 0.5-1%, the mass fraction of yttrium is 0-0.1%, the mass fraction of carbon is 0.02-0.1%, and the balance is Fe. And the material has strong corrosion resistance and preferential intergranular oxidation resistance in lead bismuth and supercritical carbon dioxide environments. The austenitic stainless steel prepared through the method is small in corrosion weight increment, small in surface oxidation film thickening and small in grain boundary oxidation depth in the high-temperature (450-650 DEG C) lead bismuth and supercritical carbon dioxide service environment, and has high corrosion resistance and preferential intergranular oxidation corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alloys, and in particular relates to a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation and a preparation method thereof. Background Art

[0002] The current range of optional materials for supercritical carbon dioxide Brayton cycle systems mainly comes from supercritical, ultra-supercritical thermal power and high-temperature, high-pressure chemical equipment materials, mainly ferrite / martensitic steel (F / M steel), (super) austenitic stainless steel, and nickel-based alloys. Existing research results show that F / M steel has obvious weight gain and thickening of oxide film in supercritical carbon dioxide environment. Under the same temperature and pressure environment conditions, the corrosion rate of austenitic stainless steel and nickel-based alloy is much lower than that of F / M steel. Under long-term corrosion of supercritical carbon dioxide, the Cr-rich oxide film formed on the surface of high-Ni, high-Cr austenitic stainless steel and nickel-based alloy will peel off and cannot maintain long-term stability. In the lead-bismuth environment, F / M steel has weaker resistance to oxidation corrosion than austenitic stainless steel; for austenitic stainless steel and nickel-based alloy, the main components of the material matrix, such as Ni and Cr, have high solubility in lead-bismuth, especially the selective dissolution of Ni in lead-bismuth, which will cause serious lead-bismuth penetration in the matrix and make the material fail. Patent CN113151747A discloses a high temperature corrosion resistant aluminum-containing austenitic stainless steel that maintains excellent thermal and chemical stability in high temperature supercritical media, but the Ni content (15-30%) of the patent design is relatively high, and it does not have the ability to resist long-term oxidation mechanism and dissolution mechanism corrosion in a high temperature lead-bismuth environment. Therefore, for the target service life of 20-30 years for the lead-bismuth reactor / supercritical carbon dioxide Brayton cycle system heat exchanger, there is currently no candidate material that can meet this condition.

[0003] In addition, austenitic stainless steel often suffers from severe preferential oxidation of grain boundaries in high-temperature corrosion environments. As a key precursor in the process of stress corrosion cracking of materials, this phenomenon generally occurs at the crack tip, inducing element diffusion and grain boundary migration, which intensifies stress corrosion cracking. A large number of studies have shown that the degree of dissolution and oxidation corrosion of (15-18)Cr-(10-15)Ni austenitic stainless steel in high-temperature lead-bismuth environments will be significantly aggravated at random large-angle grain boundaries and twins. Among them, preferential intergranular oxidation will cause cracking at the grain boundaries of the material, and lead-bismuth will penetrate and further cause the oxide film and matrix to fall off; in a supercritical carbon dioxide environment, preferential intergranular oxidation also occurs on the corrosion surface of austenitic stainless steel. Under stress loading conditions, accompanied by vacancy accumulation, a large number of cavities are formed on the grain boundaries, resulting in a decrease in the material's resistance to stress corrosion cracking, and there is a possibility of coupling with mechanisms such as carburization and creep to cause grain boundary degradation and aggravated material failure. At present, there is no candidate material that is resistant to preferential intergranular oxidation corrosion in a high-temperature lead-bismuth / supercritical carbon dioxide corrosion environment. Therefore, it is necessary to focus on the mechanism of the grain boundary oxidation problem and prepare a new austenitic stainless steel material with excellent resistance to grain boundary oxidation corrosion through composition design. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation, characterized in that: the new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation contains nickel, chromium, aluminum, manganese, silicon, niobium, yttrium, carbon and iron;

[0008] Among them, calculated by mass percentage of raw materials, the mass fraction of nickel is 12-20%, the mass fraction of chromium is 10-20%, the mass fraction of aluminum is 1.5-4.5%, the mass fraction of manganese is 1-4%, the mass fraction of silicon is 0.5-1%, the mass fraction of niobium is 0.5-1%, the mass fraction of yttrium is 0-0.1%, the mass fraction of carbon is 0.02-0.1%, and the balance is Fe.

[0009] As a preferred embodiment of the preparation method of the present invention, the mass fraction of nickel is 18%, the mass fraction of chromium is 14%, the mass fraction of aluminum is 3.5%, the mass fraction of manganese is 2%, the mass fraction of silicon is 0.6%, the mass fraction of niobium is 0.6%, the mass fraction of yttrium is 0.08%, the mass fraction of carbon is 0.04%, and the balance is Fe.

[0010] As a preferred embodiment of the preparation method of the present invention, the novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation also has the following characteristics:

[0011] (i) The oxide film thickness is less than 6.5 μm in lead-bismuth solution at 650°C for 500 hours;

[0012] (ii) The weight gain after oxidation in supercritical carbon dioxide at 650°C for 500 hours is less than 150 mg / dm2;

[0013] (iii) No obvious preferential oxidation of grain boundaries occurred in supercritical carbon dioxide at 650 °C for 500 h.

[0014] (iv) No obvious grain boundary preferential oxidation phenomenon occurred in the lead-bismuth eutectic alloy with saturated oxygen concentration at 650℃ for 500 hours.

[0015] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation.

[0016] As a preferred embodiment of the preparation method of the present invention, the pure metal raw materials Fe, Cr, Ni, Mo, Nb and Y are fully mixed according to the designed composition in a vacuum induction furnace and then placed in a crucible for vacuuming and electric melting; during the melting period, a high vacuum environment and a low melting rate are used to enhance the efficiency of carbon deoxidation and nitrogen removal, and after the steel is liquefied and cleared, the remaining C and Al are added and fully melted before refining;

[0017] After refining, argon is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content, and then cast into ingots;

[0018] The smelted steel ingot is forged and air-cooled to obtain a stainless steel forging blank, which is then polished to remove the oxide scale.

[0019] The stainless steel forging blank with oxide scale removed is heat treated to obtain a new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation.

[0020] As a preferred embodiment of the preparation method of the present invention, the steel ingot is placed in a heating furnace during the forging process, heated to 1200°C at a heating rate of 120°C / h, kept warm for 3-8 hours, and then forging begins. The final forging temperature is not lower than 925°C, and after forging, the stainless steel billet is obtained by water cooling or air cooling.

[0021] As a preferred embodiment of the preparation method of the present invention, the refining condition is to keep the temperature at 1500°C for not less than 10 minutes.

[0022] As a preferred embodiment of the preparation method of the present invention, the heat treatment conditions are as follows: the stainless steel forging blank is solution treated at 1100-1200°C for 60-120 minutes, water cooled, and then aging treated at 650-700°C for 100 hours.

[0023] As a preferred embodiment of the preparation method of the present invention, the vacuum power transmission smelting conditions are 1550-1800°C, and the power transmission power is 5-40KW.

[0024] As a preferred embodiment of the preparation method of the present invention, the start forging temperature is not lower than 1150°C and not higher than 1245°C, and the final forging temperature is 900-1050°C.

[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation for use in a heat exchanger of a lead-bismuth cooled fast reactor supercritical carbon dioxide Brayton cycle power system.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention aims at the demand for corrosion-resistant service materials for the lead-bismuth cooled reactor-supercritical carbon dioxide Brayton cycle heat exchange system. By rationally designing the composition, adjusting the content and ratio of each element in the alloy, and supplementing with processes such as heat treatment, a new type of aluminum-containing austenitic stainless steel is obtained. The material has the ability to resist high-temperature lead-bismuth and supercritical carbon dioxide corrosion.

[0028] (2) The novel austenitic stainless steel of the present invention has good high temperature corrosion resistance and resistance to preferential intergranular oxidation corrosion. The oxide film thickness is less than 6.5 μm in 650°C high temperature lead-bismuth for 1000 hours, and no obvious preferential intergranular oxidation corrosion behavior occurs. The oxidation weight gain is less than 130 mg / dm in 650°C supercritical carbon dioxide for 1000 hours. 2 . It can meet the material corrosion resistance requirements in 450-650℃ lead-bismuth eutectic alloy or 450-650℃, 20MPa supercritical carbon dioxide environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 Corrosion weight gain curves of the AFA steel provided in the embodiments of the present invention and the 316LN of comparative example 1 in supercritical carbon dioxide at 650° C. for 1000 h.

[0031] Figure 2 The cross-sectional morphology characterization results of the AFA steel provided in the embodiments of the present invention and the 316LN of comparative example 1 in saturated oxygen concentration lead-bismuth at 650°C for 1000 hours.

[0032] Figure 3 The statistical results of the corrosion degree of the AFA steel provided in the embodiments of the present invention and the 316LN of comparative example 1 in saturated oxygen concentration lead-bismuth at 650°C for 1000 hours. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0037] Example 1

[0038] The present invention provides a novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation and suitable for a heat exchanger of a supercritical carbon dioxide Brayton cycle power system of a lead-bismuth cooled fast reactor and a preparation method thereof:

[0039] By mass fraction, it includes the following components: 18% Ni, 14% Cr, 0.7% Mn, 0.6% Si, 0.6% Nb,

[0040] 0.04% C, 3.5% Al, 0.08% Y, and the balance is Fe.

[0041] (1) Use a vacuum induction furnace to mix pure metal raw materials Fe, Cr, Ni, Nb, and Y, place them in a crucible, evacuate them, and send them to melt. The melting temperature is 1500°C, and the holding time is not less than 10 minutes. After the steel is liquefied and cleared, C and Al are added to fully melt and then refined.

[0042] (2) After refining, 0.04 MPa argon gas is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content. Then, the steel is cast into ingots.

[0043] (3) The smelted steel ingot is forged. During the forging process, the steel ingot is placed in a heating furnace and first heated to 800°C at a heating rate of 100°C / h for 1-2 hours. Then, it is heated to 1200°C at a heating rate of 100°C / h for 3 hours. Then, it is cooled to 1180°C and forged after 1 hour of heating. The starting forging temperature is not lower than 1180°C and not higher than 1250°C. The final forging temperature is 950-1000°C. The stainless steel forging blank is air-cooled and polished to remove the oxide scale.

[0044] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1150℃ for 60 minutes, water cooled, and then heated at 650℃.

[0045] Perform 100 hours of aging treatment.

[0046] Example 2

[0047] The difference from Example 1 is that, calculated by mass fraction, the following are 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.05% Y, and the balance is Fe.

[0048] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1135°C for 60 minutes, water cooled, and then aged at 650°C for 100 hours.

[0049] Example 3

[0050] The difference from Example 1 is that, calculated by mass fraction, 18% Ni, 14% Cr, 2% Mn, 0.6% Si,

[0051] 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, and the balance is Fe.

[0052] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1125℃ for 60 minutes, water cooled, and then heated at 650℃.

[0053] Perform 100 hours of aging treatment.

[0054] Example 4

[0055] The difference from Example 1 is that, calculated by mass fraction, the following are 18% Ni, 14% Cr, 2% Mn, 0.6% Si, 0.6% Nb, 0.04% C, 3.5% Al, 0.08% Y, and the balance is Fe.

[0056] The heat treatment process is as follows: the stainless steel forging billet is solution treated at 1140°C for 60 minutes, water cooled, and then aged at 650°C for 100 hours.

[0057] Comparative Example 1

[0058] The difference from Example 1 is that, calculated by mass fraction, the following are 13% Ni, 18% Cr, 2% Mn, 1% Si, 0.0035% C, and the balance is Fe.

[0059] Comparative Example 2

[0060] The difference from Example 1 is that, calculated by mass fraction, 18% Ni, 14% Cr, 2% Mn, 0.6% Si,

[0061] 0.6% Nb, 0.04% C, 1.5% Al, 0.08% Y, and the balance is Fe.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that, calculated by mass fraction, 18% Ni, 14% Cr, 2% Mn, 0.2% Si,

[0064] 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, and the balance is Fe.

[0065] Comparative Example 4

[0066] The difference from Example 1 is that, calculated by mass fraction, 16% Ni, 14% Cr, 2% Mn, 0.6% Si,

[0067] 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, and the balance is Fe.

[0068] Comparative Example 5

[0069] The difference from Example 1 is that, calculated by mass fraction, 18% Ni, 16% Cr, 2% Mn, 0.6% Si,

[0070] 0.6% Nb, 0.04% C, 2.5% Al, 0.08% Y, and the balance is Fe.

[0071] Comparative Example 6

[0072] The difference from Example 1 is that, calculated by mass fraction, 18% Ni, 16% Cr, 2% Mn, 0.6% Si,

[0073] 0.6% Nb, 0.04% C, 2.5% Al, 0.2% Y, and the balance is Fe.

[0074] The materials used are shown in Table 1.

[0075] Table 1 (Unit: mass percentage)

[0076]

[0077]

[0078] Examples 1 to 4 and comparative examples 1 to 6 were subjected to corrosion tests in high-temperature lead-bismuth (650°C, saturated oxygen concentration) and supercritical carbon dioxide (650°C, 20MPa). The corrosion resistance of the design scheme was evaluated by the weight gain of supercritical carbon dioxide corrosion and the thickening of the oxide film in the lead-bismuth environment. The resistance of the design scheme to preferential intergranular oxidation was evaluated by the depth of grain boundary oxidation. The results are as follows.

[0079] Figure 1 The AFA steel provided by the embodiment of the present invention and the comparative example are subjected to corrosion weight gain curves in 650℃ supercritical carbon dioxide for 1000h. The results show that compared with comparative examples 1 to 6, embodiments 1 to 4 have smaller corrosion weight gain, indicating that the material has strong resistance to supercritical carbon dioxide corrosion, and the formed oxide film has strong protectiveness, which prevents the material from further oxidation weight gain. Compared with the embodiment, the corrosion weight gain of comparative examples 1, 2 and 3 increases, indicating that the Al and Si contents are lower than the designed components, resulting in a significant reduction in the protectiveness of the material oxide film; the corrosion weight gain of comparative examples 1, 4 and 5 increases compared with the embodiment, indicating that the reduction of Ni and Cr contents is not conducive to the formation of protective Cr and Al oxide films, and the corrosion resistance of the material is reduced; compared with embodiment 1, embodiment 2, 3, 4 and 6, the corrosion weight gain is higher, indicating that the doping of a reasonable content (0 to 0.1%) of Y element has a positive effect on the material's resistance to supercritical carbon dioxide corrosion.

[0080] Figure 2The AFA steel provided in the embodiments of the present invention and the comparative examples are characterized by the cross-sectional morphology of corrosion in 650℃ saturated oxygen concentration lead bismuth for 1000h. The results show that Examples 1 to 4 have the thinnest oxide film, indicating that the oxide film has the best protection, can prevent the material matrix from being further corroded by lead bismuth, has strong resistance to lead bismuth corrosion, does not undergo preferential intergranular oxidation, and has strong resistance to grain boundary oxidation; Comparative Examples 1, 2, and 3 show that Al and Si have a positive significance for the protection of the oxide film; Comparative Examples 1, 4, and 5 show that the reduction of Ni and Cr content is not conducive to the formation of protective Cr and Al oxide films, resulting in reduced protection of the oxide film, increased internal oxidation, and reduced resistance to lead bismuth corrosion of the material. The comparison of Examples 1-4 and Comparative Example 6 shows that doping with a reasonable content (0 to 0.1%) of Y element has a positive effect on the material's resistance to lead bismuth corrosion.

[0081] Figure 3 The statistical results of the corrosion degree of AFA steel provided by the embodiments of the present invention and the comparative embodiments in 650℃ saturated oxygen concentration lead bismuth for 1000h. The results show that embodiments 1 to 4 have the thinnest oxide film and the low degree of grain boundary oxidation, indicating that the oxide film has the best protection, strong resistance to lead bismuth corrosion, and strong resistance to grain boundary oxidation; compared with the embodiments, Al and Si have positive significance for the oxide film protection and resistance to grain boundary oxidation in comparative examples 1, 2 and 3; compared with the embodiments, the reduction of Ni and Cr content in comparative examples 1, 4 and 5 is not conducive to the formation of protective Cr and Al oxide films, resulting in a decrease in the material's resistance to lead bismuth corrosion and grain boundary oxidation corrosion, and an increase in the degree of oxidation; the comparison of embodiments 1-4 and comparative example 6 shows that the doping of a reasonable content (0 to 0.1%) of Y element has a positive effect on the material's resistance to grain boundary oxidation in a high-temperature lead bismuth corrosion environment.

[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. An austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation of lead-bismuth / supercritical carbon dioxide and a preparation method thereof, characterized in that: The novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation contains nickel, chromium, aluminum, manganese, silicon, niobium, yttrium, carbon and iron; Among them, calculated by mass percentage of raw materials, the mass fraction of nickel is 12-20%, the mass fraction of chromium is 10-20%, the mass fraction of aluminum is 1.5-4.5%, the mass fraction of manganese is 1-4%, the mass fraction of silicon is 0.5-1%, the mass fraction of niobium is 0.5-1%, the mass fraction of yttrium is 0-0.1%, the mass fraction of carbon is 0.02-0.1%, and the balance is Fe.

2. The novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation according to claim 1, characterized in that: Calculated by mass percentage of the raw materials, the mass fraction of nickel is 18%, the mass fraction of chromium is 14%, the mass fraction of aluminum is 3.5%, the mass fraction of manganese is 2%, the mass fraction of silicon is 0.6%, the mass fraction of niobium is 0.6%, the mass fraction of yttrium is 0.08%, the mass fraction of carbon is 0.04%, and the balance is Fe.

3. The novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation according to claim 1 or 2, characterized in that: The novel austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation also has the following characteristics: (i) The oxide film thickness is less than 6.5 μm in lead-bismuth solution at 650°C for 500 hours; (ii) Weight gain after oxidation in supercritical carbon dioxide at 650°C for 500 hours is less than 130 mg / dm 2 ; (iii) No obvious preferential oxidation of grain boundaries occurred in supercritical carbon dioxide at 650 °C for 500 h. (iv) No obvious grain boundary preferential oxidation phenomenon occurred in the lead-bismuth eutectic alloy with saturated oxygen concentration at 650℃ for 500 hours.

4. The method for preparing the novel uniform corrosion and grain boundary oxidation resistant austenitic stainless steel according to any one of claims 1 to 3, characterized in that: The pure metal raw materials Fe, Cr, Ni, Mo, Nb and Y are fully mixed according to the designed composition in a vacuum induction furnace and then placed in a crucible for vacuum melting. During the melting period, a high vacuum environment and a low melting rate are used to enhance the efficiency of carbon deoxidation and nitrogen removal. After the steel is liquefied and cleared, the remaining C and Al are added and fully melted before refining. After refining, argon is introduced into the induction furnace, and Si and Mn are added to further reduce the oxygen and sulfur content, and then cast into ingots; The smelted steel ingot is forged and air-cooled to obtain a stainless steel forging blank, which is then polished to remove the oxide scale. The stainless steel forging blank with oxide scale removed is heat treated to obtain a new type of austenitic stainless steel resistant to uniform corrosion and grain boundary oxidation.

5. The preparation method according to claim 4, characterized in that: During the forging process, the steel ingot is placed in a heating furnace, heated to 1200°C at a heating rate of 120°C / h, kept warm for 3-8 hours, and then forging begins. The final forging temperature is not less than 925°C. After forging, the stainless steel billet is obtained by water cooling or air cooling.

6. The preparation method according to claim 4, characterized in that: The refining condition is to keep the temperature at 1500° C. for not less than 10 minutes.

7. The preparation method according to claim 4, characterized in that: The heat treatment conditions are as follows: the stainless steel forging blank is solution treated at 1100-1200°C for 60-120 minutes, water cooled, and then aging treated at 650-700°C for 100 hours.

8. The preparation method according to claim 4, characterized in that: The vacuum power transmission smelting conditions are 1550-1800°C, and the power transmission power is 5-40KW.

9. The preparation method according to claim 5, characterized in that: The initial forging temperature is not lower than 1150°C and not higher than 1245°C, and the final forging temperature is 900-1050°C.

10. Application of the novel uniform corrosion and grain boundary oxidation resistant austenitic stainless steel as claimed in claim 1 in a heat exchanger of a lead-bismuth cooled fast reactor supercritical carbon dioxide Brayton cycle power system.

Citation Information

Patent Citations

  • Austenite heat-resistance stainless steel forming Al2O3 protective layer spontaneously

    CN101906595A

  • High-temperature and corrosion resistant aluminum-containing austenitic stainless steel and preparation method

    CN113151747A

  • Aluminum-containing austenitic stainless steel resistant to liquid lead and bismuth corrosion and preparation method of aluminum-containing austenitic stainless steel

    CN115595511A

  • Anti-coking oven tube with gradient composite oxide layer and manufacturing method of anti-coking oven tube

    CN116445182A

  • AFA alloy and preparation method thereof

    CN118086798A